Modulation of TLR4 Sialylation Mediated by a Sialidase Neu1 and Impairment of Its Signaling in Leishmania donovani Infected Macrophages - Karmakar, Joyshree; Roy, Saptarshi; Mandal, Chitra (Frontiers in Immunology, 2019)
Altered sialylation is generally maintained by a fine balance between sialidases and sialyltransferases, which plays an essential role during disease pathogenesis. TLR4 is a highly sialylated glycoprotein predominantly having α2,3-linked sialic acids. It is one of the most important client molecules in anti-leishmanial innate immune arm. Here, we initiated a comprehensive study on modulation in sialylation of TLR4 on Leishmania donovani (L.d)-infected macrophages by a mammalian sialidase/neuraminidase-1 (Neu1) having substrate specificity towards α2,3-linked sialic acids. We observed reduced membrane-associated Neu1 with decreased enzyme activity resulting enhanced TLR4 sialylation in the infected cells. Additionally, we have demonstrated decreased tyrosine-phosphorylation of Neu1 as well as reduced Neu1-cathepsinA complex on the membrane fraction of these cells which possibly play a significant role in inhibiting translocation of this sialidase from cytosol to membrane. Moreover, we demonstrated reduced association of Neu1 with TLR4 and also decreased binding of TLR4 with downstream adapter protein MyD88. Conversely, Neu1 over expression exhibited enhanced association of TLR4 with Neu1 resulting in reduced sialylation. There was an increased association of TLR4 with MyD88 which possibly linked to decreased sialylation of TLR4. Neu1 over expression further activated downstream MAP kinase signaling pathway, with enhanced nuclear translocation of NFκB that resulted in increased genetic and protein levels expression of Th1 cytokines and effector molecule nitric oxide secretion which ultimately leads to reduced parasite burden in macrophages. Taken together, our study first time demonstrated impaired translocation of cytosolic Neu1 to the membrane of L. d-infected macrophages due to impaired phosphorylation of this enzyme. This novel finding establishes a link between enhanced α2,3-linked sialic acids on TLR4 and reduced membrane-bound Neu1 which plays a significant role for inhibiting downstream signaling to establish successful infection in the host cells.